Toxicity of pharmaceutical micropollutants on common carp (Cyprinus carpio) using blood biomarkers - Walaa M. Shaalan; Alaa El-Din H. Sayed (Scientific Reports)
Abstract The presence of pharmaceutical compounds in aquatic environments has become a notable ecological issue, with compounds such as bromazepam, naproxen, metoprolol, and sotalol being of particular concern due to their prevalence and potential biological effects on non-target species. This study aims to evaluate the effects of these pharmaceuticals on common carp (Cyprinus carpio), focusing on cytogenicity, genotoxicity, hematological, biochemical, neurological, and immunological responses. Juvenile carp were exposed to 15.54 µg/L bromazepam, 14.40 µg/L naproxen, 5.76 µg/L metoprolol, and 3.33 µg/L sotalol, respectively. Hematological analysis revealed significant reductions in red blood cell counts and hemoglobin levels, indicating potential anemia, especially in fish exposed to naproxen. Biochemical assays showed increased levels of albumin, globulin, and enzymes indicative of liver stress in exposed groups. Antioxidant defense enzymes such as superoxide dismutase, catalase, and glutathione peroxidase showed significant activity increases, suggesting oxidative stress. Apoptosis assays demonstrated elevated erythrocyte apoptosis, particularly in the naproxen group, which also exhibited the highest DNA damage. These findings highlight the ecological significance of pharmaceutical contamination and highlight the urgent need for thorough environmental risk assessments that take into account the health of both organisms and ecosystems, as well as the creation of mitigation plans for their detrimental effects on aquatic ecosystems.